SISTEM INFORMASI PENCARIAN MASJID DI KOTA PAREPARE BERBASIS ANDROID - Yunus, Mughaffir; Ramadhan, Andi Muhammad Fahreza (Jurnal Sintaks Logika, 2021)
The author made a system, namely the Android-Based Mosque Search Information System in the City of Parepare which was made to make it easier for the community, especially newcomers to find the location of the nearest mosque by including the address and position of the coordinates on the GPS which can make it easier for people to find the location of the mosque that is being sought This application is made with Framework7 with a MYSQL data base where this system is online or requires an internet connection to run properly. The working system of this application is to connect the database services at the Ministry of Religion and a google map so that it can display mosque information properly to the public. Where the application manager is devoted to managing mosque data including the location of the mosque, the address, the position of mosque coordinates, etc., while the ministry of religion is in charge of managing mosque data so that the mosque data displayed is still updated.